THE IMPLEMENTATION OF EQUITY PEDAGOGY IN MULTICULTURAL ISLAMIC EDUCATION AT SMA MUHAMMADIYAH 10 SURABAYA - Wanda Katerina; Hayumuti, Hayumuti; Fazlurrahman Hadi, Muhammad (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2025)
Students lack understanding of the values of diversity and equality in the classroom, especially in a multicultural country like Indonesia. This research aims to analyse the impact faced by SMA Muhammadiyah 10 Surabaya students, especially in class XII MIA Putri. In multicultural Islamic education, applying equity pedagogy is very important to foster mutual respect between people, understand differences, and build harmonious social integration. The research method used is qualitative with the type of field study, where data is obtained through observation, interviews, and documentation. The results showed that applying equity pedagogy significantly improved students' understanding of equality values. Students show a tolerant attitude, as evidenced by social interactions in the school environment. However, challenges such as limited teacher competence in integrating multicultural values into learning and specific cultural resistance. Thus, continuous teacher training and institutional support are needed to ensure the sustainability of equity pedagogy implementation in creating an inclusive and equitable educational environment.